The current spectrum of contact sensitization in patients with chronic leg ulcers or stasis dermatitis - new data from the Information Network of Departments of Dermatology (IVDK) - Geier, Johannes; Mahler, Vera; Erfurt-Berge, Cornelia (Contact Dermatitis, 2017)
BACKGROUND: Patients with lower leg dermatitis, chronic venous insufficiency or chronic leg ulcers have a high prevalence of contact sensitization. OBJECTIVES: To identify the current spectrum of contact allergens in these patients. PATIENTS AND METHODS: Data of the Information Network of Departments of Dermatology on 5264 patients with the above diagnoses from the years 2003 to 2014 (study group) were compared with data on 4881 corresponding patients from 1994 to 2003 (historical control group) and with a current control group without these diagnoses (n = 55 510). RESULTS: Allergic contact dermatitis was diagnosed less frequently in the study group than in the historical control group (25.9% versus 16.9%; p < 0.001), and contact sensitization to most allergens had declined. The allergen spectrum, however, was largely unchanged. Important allergens are Myroxylon pereirae (balsam of Peru) (14.8% positive reactions), fragrance mix I (11.4%), lanolin alcohol (7.8%), colophonium (6.6%), neomycin sulfate (5.0%), cetearyl alcohol (4.4%), oil of turpentine (3.1%), and paraben mix (2.6%). Patch testing with additional series showed sensitization to Amerchol L-101 (9.7%), tert-butyl hydroquinone (8.7%), framycetin sulfate (5.0%), and gentamicin sulfate (3.1%). CONCLUSIONS: Topical preparations for treating the above-mentioned conditions should not contain fragrances, Myroxylon pereirae, and colophonium. The special allergen spectrum has to be considered in patch testing.
EVALuna2:35405